COCONUT BREEDING: IDENTIFICATION OF PARENTS IN MALAYAN YELLOW DWARF AND TALL CULTIVARS FOR THE PRODUCTION OF PROMISING DWARF FEMALE x TALL MALE HYBRIDS - K. Satyabalan (International Coconut Community, 1999)
Results of a study made on the nut and copra characters of Malayan Yellow Dwarf palms and of the local Tall cultivars to select the parents which could combine well, when Malayan yellow Dwarf palms as pistillate parents are crossed with Tall cultivars as pollen parents are presented in this paper. In this study Malayan yellow Dwarf palms were classified into four groups based mainly on nut characters like shell and copra content which are fairly stable characters. The Tall cultivars were classified into five groups based mainly on the copra content per nut. Correlation studies made on the important characters of the nut in the Dwarf and Tall cultivars indicated significant correlations between the stable characters shell, kernel and copra. Based on this relationship it may be possible to identify palms in both which could combine well when Malayan Yellow Dwarf as pistillate parent is crossed with the Tall as pollen parent. The study has indicated that it may be preferable to select Malayan Yellow Dwarf palms which produce nuts which have a low shell content (less than 17 percent of husked nut weight) and yield a copra content of more than 150g per nut as pistillate parent and Tall palms which yield nuts of low husk content (less than 50 percent of the weight of fruit) and a high copra content of 200g or more per nut as pollen parent. The combining ability of the parents could be ascertained form xenia studies before taking up crossing work. Individual palms from both the cultivars which can combine well can be identified and utilized for the production of a large number of hybrid seedlings in a short time.